THE IMPACT OF THE INDICATORS OF IRAQ STOCK EXCHANGE ON SOME VARIABLES OF FINANCIAL STABILITY IN IRAQ - Kadhim Saad Abdul Ridha Al-Araji; Mohammed Naji Mohammed Al-Zubaidi; Shaimaa Abdel Hadi Hussein Al Sharifi (Scholar Express Journals, 2022)
For the role played by financial exchange and the vital center in economic systems, especially in countries that depend on attracting capital through their exchange, these exchange have not played a role in enhancing their economic efficiency and their role in achieving financial stability, as the researcher concluded that the indicators of the financial exchange have an impact on the variables of financial stability and the financial exchange are linked to a positive relationship with financial stability, therefore, the researcher recommended paying attention to financial exchange, raising their efficiency through infrastructure, increasing their economic spending on other countries, and benefiting from the experiences of other countries with active financial exchange that achieve financial stability.
Keywords: Iraq Stock Exchange, Financial Stability